2014
DOI: 10.1596/1813-9450-7085
|View full text |Cite
|
Sign up to set email alerts
|

Does Land Fragmentation Increase the Cost of Cultivation? Evidence from India

Abstract: Although a large literature discusses the productivity effects of land fragmentation, measurement and potential endogeneity issues are often overlooked. This paper uses several measures of fragmentation and controls for endogeneity and crop choice by looking at inherited paddy and wheat plots to show that these issues matter empirically. While crop choice can mitigate effects, fragmentation as measured by the Simpson index increases production cost and fosters substitution of labor for machinery, especially fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…Manjunatha et al (2013) concluded that land fragmentation in India is positively and significantly associated with inefficiency. These findings confirmed those of Deininger et al (2014), who determined that fragmentation increases production costs and fosters the substitution of labour for machinery, especially for small and medium farmers in India. However, according to results from Rwanda, Ali et al (2015) argued that fragmentation tends to reduce the incidence of crop shocks and increases yields and productive efficiency; therefore, in Rwanda, interventions to reduce fragmentation may be ineffective or counterproductive.…”
Section: Doi: 1017221/180/2016-agriceconsupporting
confidence: 87%
“…Manjunatha et al (2013) concluded that land fragmentation in India is positively and significantly associated with inefficiency. These findings confirmed those of Deininger et al (2014), who determined that fragmentation increases production costs and fosters the substitution of labour for machinery, especially for small and medium farmers in India. However, according to results from Rwanda, Ali et al (2015) argued that fragmentation tends to reduce the incidence of crop shocks and increases yields and productive efficiency; therefore, in Rwanda, interventions to reduce fragmentation may be ineffective or counterproductive.…”
Section: Doi: 1017221/180/2016-agriceconsupporting
confidence: 87%
“…Different research results [11][12][13][14][15] indicated that land fragmentation is often considered as the source of inefficiencies in crop productivity which is associated with production costs due to inefficient resource allocation; suboptimal usage of factor inputs that lowers overall returns to land due to losses on extra travel time, wasted space along borders, inadequate monitoring, and the inability to use certain 2 Advances in Agriculture types of machinery; hindering agricultural modernization and making it costly to modify adverse effects by consolidation schemes; and so forth. Empirically, they estimated that land fragmentation constitutes 60% of the total cash cost of production.…”
Section: Introductionmentioning
confidence: 99%
“…For a discussion on whether land fragmentation increases the cost of cultivation in India seeDeininger et al (2017).4 There are serious concerns that surveys miss households at the very top end of the income distribution and hence underestimate inequality.…”
mentioning
confidence: 99%